2002
DOI: 10.1163/22941932-90000313
|View full text |Cite
|
Sign up to set email alerts
|

Growth and Wood Density Responses to Later-Age Fertilizer Application in Pinus Radiata

Abstract: Growth or ring width responses to nitrogen, phosphorus and the two combined fertilizers were significant over five out of seven years that followed treatment (post-treatment period) in thinned, mid-rotation radiata pine (Pinus radiata D. Don). Responses were similar between nitrogen and phosphorus treatments and largest in the nitrogen plus phosphorus (NP) treatment. Fertilizer increased the proportion of wood formed in mid-rotation relative to juvenile wood thereby increasing tree density in comparison to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
28
0
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 25 publications
8
28
0
1
Order By: Relevance
“…In relation to eucalypts, fertilizer generally either increases or has no effect on wood quality, but it increases the nutrient content of wood and hence nutrient export from sites (Raymond 1998). In conifers, fertilization that increases growth rates also tends to decrease wood density, but overall there is usually an increase in the total value of wood for sawn timber or pulpwood (Antony et al 2009;Cao et al 2008;Downes et al 2002;Nyakuengama et al 2002;Zobel 1992). Overuse of fertilizers in forestry can result in trees with multiple or contorted stems that greatly reduces the value of the tree for either pulpwood or sawn timber purpose (Turnbull et al 1994).…”
Section: Goals Of Fertilizationmentioning
confidence: 99%
“…In relation to eucalypts, fertilizer generally either increases or has no effect on wood quality, but it increases the nutrient content of wood and hence nutrient export from sites (Raymond 1998). In conifers, fertilization that increases growth rates also tends to decrease wood density, but overall there is usually an increase in the total value of wood for sawn timber or pulpwood (Antony et al 2009;Cao et al 2008;Downes et al 2002;Nyakuengama et al 2002;Zobel 1992). Overuse of fertilizers in forestry can result in trees with multiple or contorted stems that greatly reduces the value of the tree for either pulpwood or sawn timber purpose (Turnbull et al 1994).…”
Section: Goals Of Fertilizationmentioning
confidence: 99%
“…Carbon may be used for incrementing wood volume by production of new cells, or increasing wood density by stimulating fibre wall thickness (Hattenschwiler et al 1996;Ceulemans et al 2002;Nyakuegama et al 2002;Atwell et al 2003;Kilpelainen et al 2003;Smethurst et al 2003;Searson et al 2004; Thomas et al 2006). Anatomical changes to fibre cells reduce the volume of cellular voids in relation to cell wall material (Thomas et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Most fertiliser trials test the temporal response to a single fertiliser application. Several studies have shown a decrease in ring density for 5-10 years after fertilisation (Albaugh et al 2004;Nyakuengama et al 2002). A short-term decline in ring density has little impact on the average density at harvest age, and is likely to have little impact on overall wood quality (McGrath et al 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Cown and McConchie (1981) reported a possible increase in wood density with increasing annual rainfall in New Zealand. Higher soil moisture status may result in high growth rates during autumn, leading to a higher proportion of latewood and therefore higher wood density (Nyakuengama et al 2002). Improved water availability throughout the year can both extend the growing season and increase growth (Benson et al 1992a), increasing both earlywood and latewood production and possibly causing little change in density.…”
Section: Introductionmentioning
confidence: 99%